A Case Study of Needs Analysis of ESP at Naura Home Science - Maulidia Habibatur Robiah; Islam, Raudhatul (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2025)
English for Specific Purposes (ESP) has emerged as a pivotal domain within English language teaching, particularly in contexts where learners require highly specialized language skills that align closely with their academic disciplines, professional fields, or vocational tasks. This qualitative case study examines the needs analysis process at Naura Home Science. This institution prepares students for the international community service (Kuliah Kerja Nyata/KKN) program. The research investigates its influence on the development and implementation of the ESP curriculum. It highlights the importance of aligning ESP instruction with the authentic needs of learners. Data were collected through a semi-structured interview with the institution’s founder, supplemented by document analysis and observation. It involves questionnaires, stakeholder interviews, and direct observation to identify the linguistic, pragmatic, and intercultural competencies needed for effective communication in diverse international contexts. The study reveals that the needs analysis is systematic, multi-method, and iterative. It also informs a learner-centered ESP curriculum that incorporates authentic materials, task-based learning, and intercultural communication training. Despite challenges such as heterogeneous learner backgrounds and limited instructional time, continuous feedback from the needs analysis facilitates ongoing refinement of the curriculum. It demonstrates how dynamic and responsive curriculum development can better prepare students for successful participation in global community service initiatives. The study contributes valuable insights to ESP program design in specialized educational settings.